Penguatan Pengetahuan Kesiapsiagaan Terhadap Bahaya Bencana Gempa Bumi dan Tsunami bagi Siswa SMAN I Lhoknga, Kabupaten Aceh Besar - Masrurah, Zakia; Sartika, Dewi; Oktarini, Yoessi; Muhni, Akmal (Universitas Syiah Kuala, 2024)
Earthquakes and tsunamis are natural disasters that can occur anywhere and anytime. Knowledge about the dangers of natural disasters needs to be imparted to the community so that they can understand the types and levels of danger that may arise. This is necessary to enhance the community's capacity to deal with disasters. Reflecting on the occurrence of the 2004 Aceh Earthquake and Tsunami, which claimed hundreds of thousands of lives and caused hundreds of millions of US dollars in losses, increasing knowledge and understanding of disaster hazards needs to be continuously pursued. The repetition of these activities aligns the history of disaster events passed down through generations with the advancements in scientific knowledge and technological progress. Increasing knowledge of earthquake and tsunami hazards can be achieved, in part, through socialization efforts. One appropriate segment of society to receive reinforcement of knowledge through socialization activities is high school students, particularly the students of SMAN 1 Lhoknga, Aceh Besar Regency. Students are the younger generation whose roles can be agents of change within the wider community. Therefore, their role in the realm of disaster management needs to be supported by a good and competent capacity enhancement. Thus, students of SMAN 1 Lhoknga can understand the factors causing and the impacts arising from earthquake and tsunami disasters and actively participate in such events.